The Aura of the Actress - Čale Feldman, Lada (Array, 2006)
This article discusses the epistemological and methodological malaise provoked by the gendered character of the concepts used in acting theory, which necessarily compromises any discussion regarding the (im)possibility of writing a non-gender biased history of acting.